Linguistic Representation of Gender in Uzbek Family Terms - Shukurova Nodira Bahtiyor Kizi (Goodwood Publishing, 2026)
Purpose: This article aims to examine how gender is linguistically represented in Uzbek family terms. Research Methodology: This study uses a qualitative linguistic approach by analyzing selected Uzbek kinship terms, including ota “father”, ona “mother”, aka “elder brother”, opa “elder sister”, kelin “bride/daughter-in-law”, kuyov “groom/son-in-law”, qaynona “mother-in-law”, and qaynota “father-in-law”. Results: The findings show that modern gender theory has shifted beyond binary male and female models toward broader analyses of power, discourse, embodiment, technology, race, class, sexuality, disability, and global inequality. Conclusions: Uzbek family terms represent gender through lexical distinctions between male and female relatives as well as through cultural meanings attached to family roles. Limitations: This study is limited to selected Uzbek family terms and does not include broader comparative analysis with other Turkic languages. Contributions: This study contributes to linguistic and gender studies by showing how Uzbek kinship vocabulary encodes gender, social hierarchy, and cultural values within family relationships.